The Peculiarities of Social Skills of Teenagers’ Having and Not Having Vision Disorders: Comparative Aspect - Raudeliūnaitė, Rita (Acta Paedagogica Vilnensia, 2006)
The article provides the results of the research into social skills of teenagers' having and not having vision disorders. The greatest attention is given to disclosure the peculiarities of intrapersonal, interpersonal, activity and collaboration skills of these teenagers'. While trying to reach this goal firstly the model of social skills of visually impaired teenagers' was made. Its reliability was checked with the help of statistical analysis. Basing on the created model the inventory schedule was made to investigate these skills. Revealing the data of the research, that was made among 92 special schools and 119 integrate visually impaired teenagers' and 189 teenagers' not having vision disorders, we have showed some social skills peculiarities of those schoolchildren. In order to disclose the level of intrapersonal skills of those schoolchildren, key attention has been concentrated on the skills in the area of self-knowledge, self-evaluation and self-control. Said skills have a strong impact on the person's capacity to create and maintain positive mutual relationships. The data shows that self-knowledge and self-evaluation skills are lower than self-control skills. Besides, special schools teenager’s intrapersonal skills are lowest. The peculiarities of interpersonal skills of teenagers having and not having vision disorders were disclosed key attention concentrating on the skills in the area of making a contact, verbal and non-verbal contact, interactions, conflict solution. The data of the research demonstrated that contact making skills are lower than verbal, non-verbal, interactions, conflict solution skills. Special schools teenager's interpersonal skills are lowest. The peculiarities of activity and collaboration skills of those schoolchildren were disclosed key attention concentrating on the skills in the area of activity organisation, result evaluation and propitious atmosphere creation. The data shows that teenagers are more successful on the skills in the area of result evaluation than in the area of activity organisation and propitious atmosphere creation. Besides, special schools teenager's activity and collaboration skills are lowest.
Keywords: vision disorders; adolescence; social integration; social skills